KEBIJAKAN TRANSPARANSI DAN AKUNTABILITAS: MAMPUKAH MENCEGAH PENYELEWENGAN DANA DESA? - Intan Rakhmawati; Raden Sapto Hendri; Nungki Kartikasari (Jurnal Riset Akuntansi, 2021)
Transparency and accountability of village finances is a highlighted topic, because of the mistakes and potential fraud that has occurred. Whereas village finance uses the Siskeudes Version 2.0 R.0.2 application, and the village government is covered by 4 ministries, namely the Ministry of Villages, Transmigration and Development of Disadvantaged Areas (Kemendes PDTT), the Ministry of Finance, the Ministry of Home Affairs (Kemendagri), and the Ministry of Communication and Informatics (Ministry of Communication and Information). Not to mention planning and budgeting which must now be linked to data from BPS and the Ministry of Social Affairs, due to the reallocation of the Village Fund for Direct Cash Assistance (BLT). This research is an analytical descriptive type of transparency and accountability policies from 4 ministries, with the perspective of district DPMD verification. The output is an analysis of policy convergence within the framework of good government governance, to prevent misuse of the Village Fund. As a result, the researchers concluded that the accountability regulations from the Ministry of Home Affairs, the Ministry of PDTT, and the Ministry of Finance were quite integrated. The basis is Government Regulation (PP) Number 11 of 2019 and Permendagri Number 20 of 2018. Its derivative is the Priority Regulation for the Use of Village Funds of the Ministry of Health, PDTT. The initial allocation and reallocation of BLT expenditure must also be followed by a Regent Regulation. Meanwhile, implementation and evaluation regulations are issued by the Ministry of Finance. Its integration with the Village Financial System (Siskeudes) application from Financial and Development Supervisory Agency (BPKP), and the Village Development Information System (SiPeDe) of the Ministry of PDTT is sufficient to minimize errors and potential fraud. Unfortunately, this is not supported by the transparency evaluation from the Ministry of Communication and Information.